Grading Systems for Canine Urothelial Carcinoma of the Bladder: A Comparative Overview - Brambilla, Eleonora; Govoni, Veronica M. [UNESP]; Cavalca, Alexandre Matheus Baesso [UNESP]; Laufer-Amorim, Renée [UNESP]; Fonseca-Alves, Carlos Eduardo [UNESP]; Grieco, Valeria (MDPI, 2022)
The relationship between tumor morphology and clinical behavior is a key point in oncology. In this scenario, pathologists and clinicians play a pivotal role in the identification and testing of reliable grading systems based on standardized parameters to predict patient prognosis. Dogs with bladder urothelial carcinoma (BUC) were recently proposed as a “large animal” model for the study of human BUCs due to the similar morphology and metastasis locations. BUC grading systems are consolidated in human medicine, while in veterinary medicine, the BUC grading systems that have been proposed for canine tumors are not yet applied in routine diagnostics. These latter systems have been proposed, decade by decade, over the last thirty years, and the reason for their scarce application is mainly related to a lack of specific cutoff values and studies assessing their prognostic relevance. However, for any prognostic study, reliable grading is necessary. The aim of the present article was to give an overview of the BUC grading systems available in both human and veterinary pathology and provide an extensive description and a critical evaluation to support veterinary researchers in the choice of possible grading systems to apply in future studies on canine BUCs.
Keywords: BUC; Dog; Grading system; Urinary bladder; Urothelial carcinoma